2023
DOI: 10.3390/pharmacy11010018
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Value of Real-Time Medication Adherence Monitoring: A Qualitative Study

Abstract: Smart adherence products enable the monitoring of medication intake in real-time. However, the value of real-time medication intake monitoring to different stakeholders such as patients, their caregivers, clinicians, and insurers is not elucidated. The aim of this study was to explore the value different stakeholders place on the availability of smart adherence products and access to real-time medication intake data. A qualitative study design using semi-structured one-on-one virtual interviews was utilized. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…These apps display and summarize the adherence data and allow for remote access, which provides not only the ability for patients to be aware of their medication taking but also the opportunity for caregivers and health care providers to conveniently access an overview of patients’ adherence history. Research has reported that health care providers value the availability of real-time medication-taking data and perceive that access to medication adherence data can help make clinical decisions in a timely manner, thus improving health-related outcomes for patients [ 13 , 15 ]. However, although SMAPs can track real-time data, they do not ensure that the patient ingested, inhaled, or injected the medication and only provide surrogate markers for adherence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These apps display and summarize the adherence data and allow for remote access, which provides not only the ability for patients to be aware of their medication taking but also the opportunity for caregivers and health care providers to conveniently access an overview of patients’ adherence history. Research has reported that health care providers value the availability of real-time medication-taking data and perceive that access to medication adherence data can help make clinical decisions in a timely manner, thus improving health-related outcomes for patients [ 13 , 15 ]. However, although SMAPs can track real-time data, they do not ensure that the patient ingested, inhaled, or injected the medication and only provide surrogate markers for adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is room for discrepancy between the adherence data recorded and patients’ actual adherence. The ability of SMAPs to integrate with other clinical platforms such as pharmacy software, electronic medication administration record, or hospital records is also highly valued by stakeholders, especially pharmacists and physicians, as it allows them to access adherence data in a seamless manner and may reduce their workload [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the desirable features that pharmacists and caregivers value include product simplicity, portability, options to lock the product, and the ability to assist with drug inventory management. These products might allow patients to independently manage their medications and could benefit highly motivated patients interested in taking control of their health and younger older adults who are more familiar with the technology [15]. However, highly motivated patients and younger older adults may not want to use such products as they have the potential to harm their dignity because these devices are locked.…”
Section: Introductionmentioning
confidence: 99%